2019
DOI: 10.1177/2192568219839414
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Interobserver Variability for CT Scan–Based Evaluation of Posterior Ligament Complex Injury in Thoracolumbar Fractures: An International Multicenter Pilot Study

Abstract: Study Design: A multicenter, pilot study, for radiological assessment of thoracolumbar spine fractures was performed with the participation of 7 centers in Africa, Europe, Asia, and South America as a part of the AO Foundation network. Objectives: To determine the interobserver variability for computed tomography (CT) scan–based evaluation of posterior ligament complex (PLC) injury in thoracolumbar fractures. Methods: Forty-two observers including 1 principal investigator at each participating center performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“… 56 However, Maheswaran et al and Tang et al have demonstrated with increasingly high-quality CT scans that parameters such as local kyphosis, interspinous distance and interpedicular distance that can be used to determine PLC integrity without an MRI. 57 , 58 Ganjeifar et al 59 even argued that the diagnostic results of PLC injury with a CT scan were similar to those obtained by MRI in thoracolumbar burst fractures. 59…”
Section: Discussionmentioning
confidence: 88%
“… 56 However, Maheswaran et al and Tang et al have demonstrated with increasingly high-quality CT scans that parameters such as local kyphosis, interspinous distance and interpedicular distance that can be used to determine PLC integrity without an MRI. 57 , 58 Ganjeifar et al 59 even argued that the diagnostic results of PLC injury with a CT scan were similar to those obtained by MRI in thoracolumbar burst fractures. 59…”
Section: Discussionmentioning
confidence: 88%
“…This study assessed comminution as the sole measure of bony instability without considering other indicators such as vertebral height loss, kyphotic angle, load-sharing classification, or canal compromise. 27 Initially, the study refrained from evaluating these radiographic parameters due to inherent measurement errors, variations in measurement methods, and poor reliability. However, on further discussion within the AO Spine Knowledge Forum Trauma, it was decided that studying the association of those parameters with decision-making could lead to a further depth of understanding.…”
Section: Discussionmentioning
confidence: 99%
“…The standardized definitions for CT findings could explain the high inter-reader reliability on CT classification reported in that study (k = .84). 16,23,34 We previously proposed defining criteria for each CT finding based on examining the diagnostic value of various morphological features of CT findings for PLC injury. 16 For instance, we used a threshold of ISW> 4 mm, which was shown to predict PLC injury independently in MRI previously.…”
Section: Discussionmentioning
confidence: 99%